The Effects of Export Expansion Policy in Poland in the Context of Recommendations of Global Organizations - Zofia Wysokinśka (Comparative Economic Research. Central and Eastern Europe, 2019)
The aim of this paper is to present the results of an analysis and evaluation of the implementation of one of the tasks of the Strategy for Responsible Development (SRD) until 2020 (with a perspective up to 2030), adopted in Poland, which should increase Poland's foreign expansion. The paper attempts to present these results in the context of diagnoses, forecasts and recommendations (developed by experts of global organizations) regarding macroeconomic policy directions for the coming years recommended for member countries of such organizations as the International Monetary Fund, the World Bank Group, the OECD and UNCTAD/UN.
Keywords: O13; 330; Strategy for Responsible Development; foreign expansion of Poland; recommendations of global organizations; macroeconomic policy